Multiple introductions of methicillin-resistant Staphylococcus aureus ST612 into Western Australia associated with both human and equine reservoirs. - Murphy, Riley; Ramsay, Josh; Lee, Y.; Pang, S.; O'Dea, M.; Pearson, J.; Axon, J.; Raby, E.; Abdulgader, S.; Whitelaw, A.; Coombs, G. (2019)
Staphylococcus aureus is a serious human and animal pathogen. Multilocus sequence type 612 (ST612) is the dominant methicillin-resistant S. aureus (MRSA) clone in certain South African hospitals and is sporadically isolated from horses and horse-associated veterinarians in Australia. Colonization and infection by ST612-MRSA is increasing in Western Australia. Whole-genome sequencing was performed for 51 ST612-MRSA isolated from Western Australian patients and healthcare workers, South African hospital patients, Australian veterinarians and New South Wales horses. Core-genome phylogenies suggested Australian equine and veterinarian-associated ST612 were monophyletic. Individual Western Australian isolates grouped either with this equine-associated lineage or more diverse lineages related to those in South African hospitals. Bioinformatic analyses of the complete ST612-MRSA reference genome SVH7513 confirmed ST612-MRSA was closely related to ST8 USA500 MRSA. Common use of rifampicin in South Africa and equine veterinarian practice may favor ST612-MRSA in these settings. ST612-MRSA-colonized humans and horses are potential reservoirs for MRSA in Australia.